The effect of previous and current COVID-19 infections on amniotic fluid index - Muayad Al-Musawi, Sarah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: COVID-19 infection had a multisystem effect. Although it does not cross the placenta, it can cause conformational changes that affect placental function, with the possibility of a change in amniotic fluid index and the development of oligohydramnios. The aim of the study is to estimate the effect of COVID-19 previous and current infections on the amniotic fluid index. Methods: A prospective case-control study was conducted in a major maternity hospital from the 1st of April 2021 to the 1st of October 2021. 125-term pregnant ladies early in labor and had been diagnosed with COVID-19, either current or previous infection (according to serology testing IgG and IgM) were considered the case group, and 125-term pregnant ladies in labor but without COVID-19 infection as a control group. A transabdominal ultrasound was done to measure the amniotic fluid index for comparison between groups. Results: Cases of previous infection had a reduced level of amniotic fluid index (mean 9.98±4.93), which is statistically significantly lower than both the current infection and control, and the amniotic fluid index of the current infection was not different statistically from the control. Finally, it is 4.48 times more common to develop oligohydramnios if the patient had previous COVID 19 infection (odd ratio 4.48, 95% CI 10.87-1.85). Conclusion: The previous COVID-19 infection is significantly associated with decreased AFI.